Evaluation of the KOTAKU (Kota Tanpa Kumuh) Program in Babakan Surabaya Subdistrict, Kiaracondong District, Bandung City - Zain, Fajrin Meilani Azzahra; Nurrohman, Aif Nanang; Shyfa, Dandi Maulana; Shidiq, Muflih (Jurnal Perencanaan Wilayah dan Kota, 2024)
Rapid urbanization has driven the growth of slum areas in urban regions, including Babakan Surabaya Subdistrict, Kiaracondong District, Bandung City, which was prioritized for intervention through the KOTAKU program in Bandung City’s RP2KPKP 2017–2021. This study evaluates the program's achievements in Babakan Surabaya, Kiaracondong, which had the largest slum area in 2017. Using a summative evaluation method and a mixed-methods approach, data were collected through a checklist based on slum area criteria from the Ministry of Public Works and Housing's handbook, community perception questionnaires, and literature review. The analysis compared existing conditions with the criteria mentioned above and analyzed community perceptions. Road access, clean water provision, and wastewater management were deemed successful, while drainage and waste management were less successful, and fire protection was unsuccessful. Community satisfaction correlated with the assessment criteria, with high satisfaction for clean water and low satisfaction for fire protection. Slum levels will decrease from moderate to light by 2024. The KOTAKU program requires improvements, especially in fire protection.